1999
DOI: 10.1016/s0364-0213(99)00011-7
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguity, competition, and blending in spoken word recognition

Abstract: A critical property of the perception of spoken words is the transient ambiguity of the speech signal. In localist models of speech perception this ambiguity is captured by allowing the parallel activation of multiple lexical representations. This paper examines how a distributed model of speech perception can accommodate this property. Statistical analyses of vector spaces show that coactivation of multiple distributed representations is inherently noisy, and depends on parameters such as sparseness and dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
58
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 23 publications
(42 reference statements)
5
58
0
Order By: Relevance
“…Implementations of this theory using recurrent neural networks have been shown to simulate the effect of subcategorical mismatch on the lexical access process (Gaskell & Marslen-Wilson, 1997b;MarslenWilson & Warren, 1994; however, see Norris, McQueen, & Cutler, 2000). They have also been able to simulate effects of lexical competition and bottom-up mismatch without directly implemented inhibitory connections between lexical units (Gaskell & Marslen-Wilson, 1999). However, the networks reported by Gaskell andMarslen-Wilson (1997b, 1999) were unable to track lexical activations across word boundaries and were consequently incapable of identifying short words embedded in longer items.…”
Section: Modeling Spoken Word Identificationmentioning
confidence: 99%
“…Implementations of this theory using recurrent neural networks have been shown to simulate the effect of subcategorical mismatch on the lexical access process (Gaskell & Marslen-Wilson, 1997b;MarslenWilson & Warren, 1994; however, see Norris, McQueen, & Cutler, 2000). They have also been able to simulate effects of lexical competition and bottom-up mismatch without directly implemented inhibitory connections between lexical units (Gaskell & Marslen-Wilson, 1999). However, the networks reported by Gaskell andMarslen-Wilson (1997b, 1999) were unable to track lexical activations across word boundaries and were consequently incapable of identifying short words embedded in longer items.…”
Section: Modeling Spoken Word Identificationmentioning
confidence: 99%
“…When the distractor object's name did not share phonetic features with the target object's name (e.g., a raccoon opposite the carriage, or a crayon opposite the tower), there was significantly less curvature in the mousemovement trajectory. These results were interpreted as evidence for parallel partial activation of multiple lexical items competing over time (e.g., Gaskell & Marslen-Wilson, 1999;Luce, Goldinger, Auer, & Vitevitch, 1998;McClelland & Elman, 1986). 1 With a similar visual display, this kind of continuous competition is also observed in computermouse trajectories toward semantic categories for taxonomic classes (e.g., Mammal and Fish), when participants are given atypical animal exemplars to classify (e.g., whale, seal) compared to typical members of those categories (e.g., horse and trout).…”
mentioning
confidence: 99%
“…When the distractor object's name did not share phonetic features with the target object's name (e.g., a raccoon opposite the carriage, or a crayon opposite the tower), there was significantly less curvature in the mousemovement trajectory. These results were interpreted as evidence for parallel partial activation of multiple lexical items competing over time (e.g., Gaskell & Marslen-Wilson, 1999; Luce, Goldinger, Auer, & Vitevitch, 1998;McClelland & Elman, 1986). 1…”
mentioning
confidence: 99%
“…At the lexical level, the combination of excitation and inhibition controls a lexical entry's activation level, which represents how well it matches a spoken word relative to all other words in the lexicon. Distributed connectionist models (e.g., the distributed cohort model [DCM]: Gaskell & Marslen- Wilson, 1997Wilson, , 1999 use the same mechanisms but, through training, form shared representations of words in their hidden units.Activation has proven to be a productive metaphor for contemplating the dynamics of recognition within this modeling tradition. In particular, the gradedness of activation nicely captures the recognition system's sensitivity to the quality of the speech signal and the composition of the lexicon, as a host of studies have demonstrated (Connine, Blasko, & Titone, 1993; Davis, MarslenWilson, & Gaskell, 2002;Vroomen & de Gelder, 1995;Warren & Marslen-Wilson, 1987;Whalen, 1981).…”
mentioning
confidence: 99%
“…At the lexical level, the combination of excitation and inhibition controls a lexical entry's activation level, which represents how well it matches a spoken word relative to all other words in the lexicon. Distributed connectionist models (e.g., the distributed cohort model [DCM]: Gaskell & Marslen- Wilson, 1997Wilson, , 1999 use the same mechanisms but, through training, form shared representations of words in their hidden units.…”
mentioning
confidence: 99%